Pengaruh Dana APBD terhadap Indeks Pembangunan Manusia (IPM) dan Pertumbuhan Ekonomi di Kabupaten Kerinci - Aditya, Hanif Daffa; Mailindra, Wiyan; Amali, Muhammad (Ekonomis: Journal of Economics and Business, 2024)
This research aims to find out and analyze how much influence the APBD has on the Human Development Index (HDI) and economic growth. The data used in this research are Kerinci Regency APBD data, HDI and economic growth for the 2013-2022 period obtained from the Central Statistics Agency (BPS). The method used is descriptive quantitative using a simple linear regression analysis tool. The results of this research show that the APBD has a positive and significant effect on the Human Development Index (HDI) and economic growth in Kerinci Regency during the 2013-2022 period.